PENGARUH KNOWLEDGE SHARING, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. HEROINTI NUSA DENPASAR - I Putu Ngurah Rizky Andika; I Gede Rihayana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2024)
This study aims to determine the effect of knowledge sharing, motivation and work environment on employee performance. The population in this study were all employees of PT Herointi Nusa Denpasar. The sample in this research amounted to 50 respondents using saturated sampling. By using a questionnaire to collect primary data, and the respondents were 50. The technique used regression analysis to determine the effect of knowledge sharing, motivation and work environment on employee performance. The results show multiple linear regression analysis, namely the T test shows Knowledge sharing has a positive effect on employee performance with a coefficient value of 0.168 and a significance of 0.011 where this value is below 0.05. Motivation has a positive and significant effect on employee performance with a coefficient value of 0.615 significance 0.001 where this value is below 0.05. The work environment has a positive and significant effect with a coefficient value of 0.690 and a significance of 0.001 where this value is below 0.05.